Space of Functions with Some Generalization of Bounded Variation in the Sense of de La Vallée Poussin - René Erlín Castillo; Humberto Rafeiro; Eduard Trousselot (Journal of Function Spaces)
We introduce a function space with some generalization of bounded variation in the sense of de la Vallée Poussin and study some of its properties, like embeddings and decompositions, among others.